MARKET EQUILIBRIUM IN THE NEW S-CURVE IN THAILAND AFFECTED BY THE DIGITAL TRANSFORMATION - Poompruk, Chanattee; Erbim, Nanthanit (RMUTT Global Business and Economics Review, 2021)
This academic paper discusses the balance of the market in the industry of the future (New S-curve), due to the rapid change in technology today. More technology is being used to create a commercial advantage. Either the manufacturer or the service provider needs to adapt to keep up with modern technological changes and innovation. And in many sectors of the manufacturing industry, it cannot be adjusted quickly. Due to the conditions of the manufacturer and the consumer in many products, changes in the market equilibrium have occurred. At the same time, in the industrial development strategy of the country, it is important to emphasize the readiness of the industry of the future (New S-curve), as a result, the market equilibrium problem occurs both on the demand and supply side. It is time to focus on the future industrial market equilibrium shift from the digital age. So that all of the above are the mechanisms driving the economy of the country that will create the growth and create the greatest potential in the Thai industry.